Grain Maturity and Sedimentary Processes of the Early Miocene Semilir Formation, Ngoro-oro Gunungkidul, Yogyakarta - Rizky, Aga; Isnani, Desi Kumala; Widada, Sugeng; Pratomo, Septyo Uji; Tony, Brian (Institut Teknologi Adhi Tama Surabaya, 2025)
The texture of sedimentary rocks is a fundamental aspect of sedimentation, reflecting the physical properties of particles and their relationships. Understanding rock texture is essential for interpreting depositional mechanisms and environments. Grain maturity represents a key property within sedimentary textures. The Early Miocene Semilir Formation is characterized by turbidite deposits with tuffaceous lithologies; however, the transport mechanism remains unclear. This study aimed to analyze the sedimentation process of the Semilir Formation by observing grain maturity. Granulometric analysis was conducted on three rock samples from the Ngoro-oro area, Gunungkidul Regency, Yogyakarta. The samples were ground, separated into size fractions, and statistically evaluated to determine quartiles, median diameter, sorting coefficient, skewness, and kurtosis. The results showed that the Semilir Formation consisted of immature grain sedimentary rocks, indicating that the sediments were deposited under moderate to high energy conditions. These findings suggest that the deposits were derived from a nearby source and were strongly influenced by volcanic slopes and underwater volcanic activity.Keywords: Grain maturity; Granulometric analysis; Sedimentary process; Semilir Formation